Dietary vitamin E intake by older Japanese adults - Hirayama, Fumi; Lee, Andy; Yasukawa, K. (Nova Biomedical, 2013)
Background: The importance and health benefits of vitamin E are well known, while the nutritional requirements of older adults are different from those of younger adults. Objective: This study investigated the quantity of dietary vitamin E intake by gender and age groups among older Japanese adults. Methods: A total of 617 eligible participants (516 men and 101 women) aged 55 to 75 years were recruited from 10 districts or prefectures in central and southern Japan. A validated and reliable food frequency questionnaire was administered face-to-face to obtain information on habitual food and beverage consumption. Dietary vitamin E intake was derived from the Japanese food composition tables. Results: Men had significantly lower habitual intake of vitamin E (mean 5.89, SD 2.60 mg/day) than women (mean 6.73, SD 2.84 mg/day) overall (p = 0.004) and across older age groups 61-70 and 71-75 years. However, their intake levels did not vary substantially between age groups. The Japanese government has recommended an intake level of 7.0 mg per day for men and 6.5 mg per day for women. It is alarming that 72% of participants did not have sufficient intake of vitamin E from dietary sources. Conclusion: Older Japanese adults especially men should be encouraged to increase their dietary intake of vitamin E in order to maintain their health and well-being.